2016
DOI: 10.1093/ee/nvw006
|View full text |Cite
|
Sign up to set email alerts
|

Identifying a Potential Trap Crop for a Novel Insect Pest,Halyomorpha halys(Hemiptera: Pentatomidae), in Organic Farms

Abstract: The invasive brown marmorated stink bug, Halyomorpha halys, poses significant risk to organic farming systems because they rely on biological control, nonsynthetic inputs, and cultural tactics for pest management. This study evaluated the potential of five crop plants (sorghum, admiral pea, millet, okra, and sunflower) to be used as trap crops under organic production in four mid-Atlantic states. Stink bug (H. halys and endemic species) densities and host plant phenologies were recorded weekly (mid-June throug… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
41
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(42 citation statements)
references
References 17 publications
1
41
0
Order By: Relevance
“…Halyomorpha halys is extremely polyphagous, feeding on 100+ species of plants (Leskey et al ., ; Rice et al ., ; http://www.stopbmsb.org). However, even for such a generalist, previous work has demonstrated that certain crop species, such as sorghum and sunflower, are more attractive than other crops to H. halys (Nielsen et al ., ). Specifically, a trap crop of sunflower and sorghum has been shown to be promising in attracting and retaining H. halys adults compared with a cash crop of bell pepper (Soergel et al ., ; Blaauw et al ., ).…”
Section: Discussionmentioning
confidence: 97%
“…Halyomorpha halys is extremely polyphagous, feeding on 100+ species of plants (Leskey et al ., ; Rice et al ., ; http://www.stopbmsb.org). However, even for such a generalist, previous work has demonstrated that certain crop species, such as sorghum and sunflower, are more attractive than other crops to H. halys (Nielsen et al ., ). Specifically, a trap crop of sunflower and sorghum has been shown to be promising in attracting and retaining H. halys adults compared with a cash crop of bell pepper (Soergel et al ., ; Blaauw et al ., ).…”
Section: Discussionmentioning
confidence: 97%
“…As plants mature, their palatability and thus suitability for insect development changes (e.g., Schumann and Todd, 1982;Awmack and Leather, 2002;Nielsen et al, 2016). We established that H. halys nymph attraction to host plants changes with plant growth stage.…”
Section: Discussionmentioning
confidence: 99%
“…One such tactic uses weekly border insecticide applications in peach orchards along with a suite of other integrated pest management (IPM) tactics to reduce overall insecticide usage . Nielsen et al . demonstrated a differential attraction of H. halys to various crops, particularly sorghum and sunflower.…”
Section: Introductionmentioning
confidence: 99%
“…One such tactic uses weekly border insecticide applications in peach orchards along with a suite of other integrated pest management (IPM) tactics to reduce overall insecticide usage. 24 Nielsen et al 25 demonstrated a differential attraction of H. halys to various crops, particularly sorghum and sunflower. However, trap cropping using a border of sunflower and sorghum, 26,27 which have been shown to arrest H. halys movement into the cash crop, 28 was not successful at reducing damage to bell peppers.…”
Section: Introductionmentioning
confidence: 99%